Genetic diversity and haplotype analysis of yak and sheep echinococcal cysts isolates from the mitochondrial cox1 gene in parts of Tibet, China - Fan, Shijie; Zhao, Xialing; Danqulamu,; Shi, Bin; Tang, Wenqiang; Dong, Hailong; Xia, Chenyang (Frontiers in Veterinary Science, 2022)
Echinococcosis, also known as hydatid disease, caused by the metacestode stage of the species cluster Echinococcus granulosus sensu lato(E. granulosus s.l.). Echinococcosis is almost widespread all over the world, especially in countries and regions dominated by animal husbandry. It is a major parasitic disease that seriously endangers human health, public health safety, environmental safety and the development of animal husbandry production in western China. In this study, the mitochondrial cox1 gene were used to analyze the genetic diversity and haplotype of bovine and sheep echinococcal cysts isolated in Tibet. Up to now, Echinococcus granulosus sensu stricto(E. granulosus s.s., G1, G3) were still the dominant species in the infected samples of yak and sheep in some parts of Tibet. Through haplotypes analysis, Hap_1 was the dominant haplotype, and 14 of the 20 haplotypes were similar to the reference sequence previously published in Genbank, and the rest of 6 haplotypes were found for the first time. Through the Tajima's D value, neutral test Fu's Fs analysis and haplotype network map, it can be considered that Echinococcus population expansion has occurred in Xigaze, Tibet. This study provides basic data for understanding the genetic characteristics, epidemiology and control of echinococcosis in this area.